THE POTENTIAL OF MUKBANG CONTENT ON YOUTUBE FOR THE CONNECTION BETWEEN KOREAN FOOD CULTURE AND VIETNAM YOUTH (Proceedings of the World Conference on Media and Mass Communication, 2023)
The media's relentless efforts to promote one country's cuisine to other countries are immense. The mukbang (online dining) trend has recently become a strong trend in the media industry, more than food technology. According to the research, mukbang has the potential to promote the multinational culture that is now a promising national cuisine. This research paper tested using a combination of methods and identified prominent cultural factors that could be considered for inclusion in mukbang content that could be viewed by media, advertisers or countries. consider applying and expanding the research to put into practice the promotion of national culinary culture.Previous studies of mukbang have, for the most part, pointed to the mental and physical health problems associated with watching mukbang as well as its effects on the human body. However, the preceding studies have not taken into account the trend's strong communicativeness as a promising form of advertising for the food industry, which is a country's culinary culture in its advertising. The study will examine the potential of this type of food through dishes of Vietnamese culinary culture appearing on Mukbang content and shown in Korea.Through the method of analyzing content coming from mukbang videos posted by Koreans using dishes imbued with Vietnamese culinary culture, the study analyzes and considers the possibility of promoting Vietnamese culinary culture through this type. In addition, through quantitative methods and analysis using the SPSS platform, this advanced research paper examines the awareness of Vietnamese youth about this form of culinary culture promotion in the potential to promote and expand the culture of Vietnamese cuisine. National cuisine in other countries where it is intercultural.According to the results of an experimental study using a combination of many research methods, it has been shown that at least 8 cultural factors are included in the current popular mukbang content and through the survey as well. The analysis of these factors contributes to increasing the influence of Korean culinary culture to reach foreign audiences, but here specifically Vietnam. The results can be seen as very promising because of the mukbang trend. has the potential to become a new form of advertising for the food industry in the media. When using mukbang content in combination with content promoting a country's culinary culture, there will be potential effects. This study also pioneers in examining the potential of this type of research and its application as a new form of advertising.Keywords: Mukbang, culture, media, youth, advertising.
Keywords: Mukbang, culture, media, youth, advertising